The Effectiveness of Independent Learning on Student Mathematical Learning Outcomes in Online Learning - Rizki, Nopia; Darmayanti, Rani; Sugianto, Rahmad; Choirudin; Muhammad, Ilham (Jurnal Dimensi Matematika, 2023)
Learning independence is something that plays a very important role in improving student learning outcomes, so that both educators and other parties must pay attention to the learning independence possessed by students. This study aims to determine the effectiveness of student learning independence on learning outcomes in online learning. The method used in this research is SLR (Systematic Literature Review). In this study identification, assessment, and description of the results of the research will be carried out. In this study the researcher will review and systematically identify articles/journals which at each stage are in accordance with what has been determined. Data was collected through documenting journals obtained in literature studies. The number of journals reviewed by researchers is 10 accredited national journals related to the chosen theme, sourced from Google Scholar and Mendeley. These journals are selected based on certain criteria to obtain relevant data. These criteria include (1) there is the name of the author, (2) there is a research title, and (3) Relevant. Based on the literature review that has been done, that student learning independence has an important role in improving learning outcomes, especially in today's online learning. Learning independence has a positive influence on student learning outcomes in online learning.